(untitled) (Revista Apotheke, 2025)
This essay presents a specific reflection on an experience of scientific initiation, in addition to a direct dialogue with some of the results of the research itself. It is a theoretical-practical study on the relationship between literature and the visual arts, drawing on the power of critical reading as originating from scientific products, but also, and above all, from creative productions in other languages and medias. Using Irina Rajewski’s concept of “media transposition” (2012), we undertook the reading and transcreation of the novel ‘Porto Calendário’ (1962), by Osório Alves de Castro, in the artistic language and medium of drawing on paper, in order to elicit critical and creative responses to the inter-artistic and inter-media dialogues involved. As one of the results, we understand that transcreation, or creative translation (Campos, 2006), between different languages and media can also be a powerful way of crafting other stories about memories and cultures, which are often stigmatized with dangerous single narratives, to paraphrase the warning of Nigerian writer Chimamanda Adichie (2009).